2002
DOI: 10.1155/2002/567090
|View full text |Cite
|
Sign up to set email alerts
|

Combined Topical and Oral Antimicrobial Therapy for the Eradication of Methicillin‐Resistant Staphylococcus aureus (Mrsa) Colonization in Hospitalized Patients

Abstract: OBJECTIVE: How to eradicate methicillin-resistantStaphylo-coccus aureus(MRSA) colonization in hospitalized patients is uncertain. We reviewed our experience with MRSA decolonization therapy in hospitalized patients.SETTING: An 1100-bed, university-affiliated tertiary care teaching hospital in Toronto, Ontario.DESIGN: Retrospective chart review of 207 adult inpatients with MRSA colonization hospitalized between February 1996 and March 1999.INTERVENTIONS: All patients with MRSA colonization were assessed for pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Many previous studies (13)(14)(15)(16)(17)(18)20,21) investigating MRSA decolonization strategies have been compromised by small sample size, tendency to exclude patients with multiple indwelling catheters and limited follow-up. The present study highlights the fact that even in a relatively unselected cohort, the mean duration of successful decolonization exceeded one year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies (13)(14)(15)(16)(17)(18)20,21) investigating MRSA decolonization strategies have been compromised by small sample size, tendency to exclude patients with multiple indwelling catheters and limited follow-up. The present study highlights the fact that even in a relatively unselected cohort, the mean duration of successful decolonization exceeded one year.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane collaboration review (13) of six randomized controlled trials studying MRSA decolonization concluded that there was insufficient evidence to support the use of decolonization. Despite these data, decolonization in selected patients is frequently performed in many hospitals (14).…”
mentioning
confidence: 99%
“…Failure of MRSA eradication therapy has often been attributed to colonization of extranasal sites (2,17,20). No consensus exists regarding the number of follow-up cultures that should be obtained after MRSA eradication therapy to assess the success of treatment.…”
mentioning
confidence: 99%
“…• The recommended regimen for nasal decolonization for mupirocin-susceptible isolates is mupirocin ointment to the nares twice daily for five to 10 days (133,134,140).…”
Section: Recommendationsmentioning
confidence: 99%
“…• A combined strategy of intranasal mupirocin, topical antiseptics and systemic antibiotics (active against the colonizing strain and achieving high levels in body secretions [eg, rifampin or clindamycin]) may be considered (140). (BIII) 8.0 POPULATION SURVEILLANCE 8.1 Population surveillance program for CA-MRSA The Working Group meeting identified several possible purposes of a population surveillance program: to document the emergence of resistance to methicillin among community isolates of S aureus to inform empirical therapy; to describe the occurrence and impact of severe S aureus disease in a community, irrespective of resistance pattern; and to facilitate timely identification of potential outbreaks.…”
Section: Recommendationsmentioning
confidence: 99%